Application of Structural Equation Modeling (SEM) to Analyze the Factors Influencing Purchase Decisions of Lampung Traditional Handicraft Products in Gunung Sugih - Ahmad Imron; Sangidatus Sholiha; Fajri Arif Wibawa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines factors influencing consumer purchase decisions for traditional handicraft products in Lampung, where local cultural potential has not been fully transformed into economic strength due to weak marketing strategies. Using a quantitative causal approach, data were collected from 100 respondents through convenience sampling and analyzed with PLS-SEM using SmartPLS 4. The results indicate that product quality, uniqueness, service quality, and digital marketing have a significant positive effect on purchasing decisions, while price does not show a significant influence. The model explains 68.1% of the variance in buying behavior, demonstrating strong predictive power. The findings suggest that consumers prioritize uniqueness, quality, and effective digital marketing over price considerations. This study contributes to educational and entrepreneurial development by providing practical insights for marketing strategy formulation. entrepreneurship education, digital marketing learning, and product creativity, while supporting the application of marketing and entrepreneurship theories in educational and practical contexts.